2018
DOI: 10.5435/jaaosglobal-d-18-00078
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Mobile Apps for Video Conferencing to Follow Patients at Home After Outpatient Surgery

Abstract: Introduction:Outpatient surgery has a great opportunity to demonstrate the role of using mobile video conference (VC) postoperatively. Our patients use technology to help decision making in finding physicians. The authors aim to assess patient's perception on the use of mobile apps for VC with the surgeon and/or staff.Methods:Consenting patients completed a questionnaire of 10 questions preoperatively and postoperatively to assess the difference in opinion.Results:Overall, 120 patients completed the questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Pencle et al. 13 created a mobile video conference application for communication with patients perioperatively. They found more than 86% of patients directly contacted either the surgeon or the concierge team before the first postoperative visit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pencle et al. 13 created a mobile video conference application for communication with patients perioperatively. They found more than 86% of patients directly contacted either the surgeon or the concierge team before the first postoperative visit.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of digital media (i.e., video calls, recorded video message, pictures) has been shown to improve patient satisfaction and engagement. 2 , 12 , 13 , 14 Evolving technology continues to provide opportunities to improve the patient experience; however, to fully use them, we must understand what information patients find beneficial and how they use it.…”
mentioning
confidence: 99%
“…Finally, 23 related articles were comprehensively surveyed for final analysis. Qualitative analysis of research-based apps showed that the common components of surgical patients' follow-up apps consist of tele-visits by examining of quality of recovery (QoR) or other indicators [ 2 , 5 , 12 , 13 , 15 , 17 , 29 32 , 34 36 , 38 , 40 – 42 , 44 , 45 ], assessing post-operative body function and pain level status by virtual analog scale (VAS) [ 2 , 12 , 15 , 17 , 29 , 32 , 36 , 40 , 41 , 44 ]; wound telemonitoring via recorded and transmitted SSI-related symptoms and images [ 2 , 5 , 13 , 17 , 19 , 29 , 35 , 36 , 40 43 ], teleconsultation, and patient connections with clinical staff [ 19 , 30 , 31 , 38 40 , 43 ], reminders and alerts [ 15 , 33 , 34 , 40 , 41 , 45 ], and patient education [ 15 , 33 , 34 , 39 , 42 , 43 , 45 ]. In most studies, fourteen [ 5 , 12 , 19 , 30 , 31 , 39 ,…”
Section: Resultsmentioning
confidence: 99%
“…Overall functional status was evaluated using the Mayo Elbow Performance Score (MEPS) and the Quick Disabilities of the Arm, Shoulder and Hand score (QuickDASH). 2 If patients were unable to undergo follow-up in the office, their elbow range of motion was assessed via digital photography 24 , 27 and the MEPS and QuickDASH questionnaires were filled out electronically. Of the 27 patients included in the study, only one patient did not attend the functional evaluation in person or electronically, although there was an electronic medical record of the other clinical variables.…”
Section: Methodsmentioning
confidence: 99%